2007
DOI: 10.1002/chem.200701234
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Control of Protein Recognition with Amino Acid‐ and Dipeptide‐Functionalized Gold Nanoparticles

Abstract: Amino acid and dipeptide-functionalized gold nanoparticles (NPs) possessing L/D-leucine and/or L/D-phenylalanine residues have been constructed in order to target the surfaces of alpha-chymotrypsin (ChT) and cytochrome c (CytC). Isothermal titration calorimetry (ITC) was conducted to evaluate the binding thermodynamics and selectivity of these NP-protein interactions. The chirality of the NP end-groups substantially affects the resultant complex stability, with up to 20-fold differences seen between particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 95 publications
1
46
0
Order By: Relevance
“…Rotello et al have shown that chiral phenylalanine (Phe) more remote from the surface of the AuNPs (C 24 spacer) does not induce optical activity in MBETs, despite the possibility of H-bonding and p-p interaction between the Phe moieties. [82] These last two examples show that there is probably a relationship between the g max factor and the distance of the chiral center from the NP surface. This phenomenon suggests that mechanism B has an effect on the optical activity.…”
Section: Ligand Effectmentioning
confidence: 94%
See 1 more Smart Citation
“…Rotello et al have shown that chiral phenylalanine (Phe) more remote from the surface of the AuNPs (C 24 spacer) does not induce optical activity in MBETs, despite the possibility of H-bonding and p-p interaction between the Phe moieties. [82] These last two examples show that there is probably a relationship between the g max factor and the distance of the chiral center from the NP surface. This phenomenon suggests that mechanism B has an effect on the optical activity.…”
Section: Ligand Effectmentioning
confidence: 94%
“…[118] Similarly, Rotello et al have clearly demonstrated by calorimetric studies that NPs bearing enantiomeric and diastereoisomeric end groups have distinctly different binding affinities towards protein targets. [82] They further demonstrated that trimethylammonium-funtionalized AuNPs protected with mixed monolayers can stabilize peptides in water through favorable interactions on templation of the NPs to the peptide surface. [119] This enhances the potential of AuNPs in helix recognition.…”
Section: Chiral Discriminationmentioning
confidence: 97%
“…The review paper on "Chemical Strategies for Generating Protein Biochips" by Jonkheijm et al (Jonkheijm et al, 2008) describes different approaches using covalent and non-covalent immobilization chemistry are reviewed. Recent studies demonstrated that the incorporation of chiral molecules onto nanoparticles provides new opportunities for achieving specificity in the recognition of protein surfaces (You et al 2008). Immobilization of trypsin on superparamagnetic nanoparticles allows using higher enzyme concentrations, leading to shorter www.intechopen.com digestion time than free enzyme molecules and easy separation from the solution (Y.…”
Section: New Photonic Methodology Used To Create Functional Nanopartimentioning
confidence: 99%
“…Recently, Rotello and coworkers fabricated a series of amino acid-and dipeptide-terminated monolayer coated nanoparticles which display hydrophobic leucine and/or phenylalanine residues, in both their d and l forms, to target the surfaces of ␣-chymotrypsin and cytochrome c [125]. They demonstrated the incorporation of chiral molecules onto monolayer-protected nanoparticles caused subtle structural changes to the nanoparticle surface leading to significant alterations of their specificity in the recognition of and affinity toward target protein surfaces manifesting in up to a 20-fold attractive difference compared to nanoparticles of similar hydrophobicity.…”
Section: Small Molecule Ligandsmentioning
confidence: 99%